Quality of sexual life after limb amputation - Kowal, Weronika; Zelek, Katarzyna; Biegańska-Banaś, Joanna; Makara-Studzińska, Marta (Nursing Problems / Problemy Pielęgniarstwa, 2024)
Amputation is an operation used as a last resort when all other treatments have failed to save a limb. It is a traumatic procedure, leading to a change in lifestyle, social status, relationships, and one’s body image, all of which affect sex life and sexual satisfaction. The aim of the study was to analyse the available literature regarding the impact of amputation on sex life and sexual satisfaction. The authors considered sexual difficulties faced by amputees, factors associated with their occurrence, and actions that can be taken in order to answer the needs of patients in this clinical group. A literature review confirmed that amputation surgery negatively impacts sex life. Patients’ condition after amputation may be characterised by a disturbed perception of their own body, which is a predictor of sexual dysfunction disorders in this group. Patients can benefit from several therapeutic and educational activities, including alternative methods of pain relief and helpful information provided by healthcare representatives and specialised foundations. A review of the available research indicates a lack of concrete systemic and procedural actions to combat the problems de-scribed in this paper.